Math
posted by Hannah .
Differentiate
g(x)=(x^3+1)(3x^21)
so I use g'(x) X h(x) + g(x) X h'(x)
so the derivative of (x^3+1)=3x^2
and (3x^31)=6x
So (3x^2)(x^3+1) + (x^3+1)(6x) Is this correct so far. If so this is where I am stuck. I am having trouble simplifing.

You made a mistake applying the "derivative of a product" formula.
g'(x) = (3x^2)(3x^21) + (x^3+1)*6x
= 12x^4 3x^2 +6x
= 3x(4x^3 x^2 +2) 
Actually I figure it out.

In google type: calc101
When you see list of resultc click on:
Calc101com Automatic Calculus and Algebra Help
When page be open clik option: derivatives
When this page be open in rectacangle type:
(x^3+1)(3x^21)
and click options DO IT
You will see solution stepbystep
By the way on this site you can practice any kind of derivation. 
Thank You!!